Dolomitic calcretes from the Changhsignian (Upper Permian) red beds of the Orenburg Cis-Urals, Russia - F.A. Mouraviev; N.M. Khasanova; E.Z. Yunusova (Учёные записки Казанского университета: Серия Естественные науки)
The dolomitic calcrete profiles from the Boyevaya Gora and Tuyembetka sections, both represented by the uppermost Permian (Changhsignian) red continental deposits from the Orenburg Cis-Urals, were studied by sedimentological, mineralogical, and geochemical methods. Сalcrete from the Boyevaya Gora section formed on sandy-silty flat alluvial fan/sheetflood sediments, under the setting of slow subsidence of the territory. Calcrete from the Tuyembetka section developed on relatively elevated mudflat/playa under a stable tectonic regime. The subtropical semi-arid climate was reconstructed based on the geochemical indices from the illuvial paleosol horizons. The presence of anhydrite in the calcrete profiles indicates the saline conditions of soil waters. Cryprocrystalline idiomorphic grains (1–3 μm) and the low Mn2+ partitioning ratio between the Ca- and Mg-position in dolomite (0.7–1.8) suggest its primary origin and a rapid crystallization from the soil waters. Free organic radicals and phosphorus-associated anion centers in the pedogenic dolomite identified by the electron paramagnetic resonance (EPR) analysis assume a biogenic contribution to the formation of dolomite. Fossilized fungal hyphae and bacteriomorphs along with the fragments of plant roots were detected by scanning electron microscopy (SEM) in both calcretes. The bacterial origin of dolomite from the studied calcretes was discussed.